WHAT DRIVES RETURN OF SUKUK IN THE LONG AND SHORT TERMS? - Bella, Firsty izzata; Chalid, Fitria Idham; Rusgianto, Sulistya (IAIN Tulungagung, 2021)
This study aims to determine the effect of liquidity, inflation, and interest rates on the return of State Retail Sukuk (SUKRI) both in the short term and in the long term. Sampling in this study used a purposive sampling method by considering that the maturity of the series is the most recent and can be obtained in the secondary market and the data sources obtained from the monthly statistical reports of the Indonesia Stock Exchange (idx.go.id), the official website of Bank Indonesia (bi.go.id), as well as through a special request to The Indonesia Capital Market Institute (TICMI). Analysis of the data used in this study is a time series, namely research that is measured over a certain period of time. The period data used was in March 2017 on the grounds that the 009 Retail Sukuk as the object of this study were published in that month and ended in March 2020. The method used in this study is ARDL-ECM after going through the stationarity test and cointegration test. The results show that in the long term only the BI rate variable has a significant positive effect on Sukuk Returns, while in the short term only the Liquidity variable has a significant effect on Sukuk Returns. On the other hand, the inflation variable is known to have no significant effect on the Sukuk Returns in the long and short term. This research can be a reference for investors to make decisions in choosing SUKRI as their investment portfolio, as well as a consideration for the government in regulating risk management policies and determining the results offered to SUKRI which will be issued for subsequent series.